Seleção e estimulação em culturas de calos de Byrsonima gardneriana A. Juss. para produção de antocianinas - Porto, Katiane Oliveira (2018)
he species Byrsonima gardneriana A. Juss. belongs to the family Malpighiaceae and presents an important economic importance due to phytochemical potential and to present anthocyanins in its callus. The objective of this work was to select cell lines and to establish a protocol to stimulate the production of anthocyanins in callus of Byrsonima gardneriana A. Juss.. The callus were induced from leaf explants obtained from plants established in vitro, using half-saline MS culture medium, solidified with 7% agar, supplemented with 30% sucrose, 16μM 6-benzylaminopurine (BAP) + 2μM naphthaleneacetic acid (ANA). The growth curve of the callus and anthocyanin content was determined at each 7 day interval. After the callus induction, three cell lines were obtained from the staining, maintained throughout five subcultures. Stimulation was performed by the addition of mannitol to the culture medium inducing osmotic stress, by exposure of callus to UV-C radiation at different time intervals and by the interaction of plant regulators added to the culture medium. The extractions and quantifications were performed by the single pH method and the extracts readings were done in a spectrophotometer. The results obtained show that it is possible to induce B. gardneriana callus from the adopted conditions; the linear growth phase, observed between 21 and 56 days of cultivation, is the recommended period for the subculture of callus of the species; at 21 days of cultivation the best relationship between anthocyanin content and callus mass is verified; selection of strains and subcultures was efficient in the second cycle in only one of the strains; the addition of 5g L-1 of mannitol to the culture medium is efficient in stimulating the production of anthocyanins in callus of the species; UV-C radiation as well as exposure time were not efficient to induce increased biosynthesis of the metabolite under study; despite the trend of higher production of anthocyanins in callus cultivated in the presence of BAP, new studies should be conducted, seeking a better understanding of the effect of plant regulators on the stimulation of the production of this pigment.